A Low Complexity Linear Precoding Method for Extremely Large-Scale MIMO Systems - Berra, Salah (2024)
Funding information: This work was supported in part by Fundação para a Ciência e Tecnologia (FCT) under the projects Copelabs UIDB/04111/2020 (https://doi.org/10.54499/UIDB/04111/2020), and in part by Instituto de Telecomunicações UIDB/50008/2020 (https://doi.org/10.54499/UIDB/50008/2020), in part by CELL-LESS6G 2022.08786.PTDC (https://doi.org/10.54499/2022.08786.PTDC), and in part by JST ASPIRE under Grant JPMJAP2325. Publisher Copyright: © 2020 IEEE.